Myocardial fibrosis in primary aldosteronism - Chen, Yi-Lin; Chen, Chi-Hua; Ye, Xiao-Fei; Xu, Jian-Zhong; Zhu, Li-Min; Xu, Ting-Yan; Li, Yan; Wang, Ji-Guang (Frontiers in Endocrinology, 2025)
ObjectiveWe investigated myocardial fibrosis in relation to clinical and biochemical characteristics and the metabolomics in patients with primary aldosteronism.MethodsOur study included 54 patients with primary aldosteronism. We performed cardiac magnetic resonance to evaluate focal replacement myocardial fibrosis defined as late gadolinium enhancement (LGE) and diffuse interstitial fibrosis as assessed by extracellular volume (ECV) with T1 mapping. We collected information on demographics and data of clinical biomarkers, and performed echocardiography and metabolomic analysis.ResultsPatients with LGE (n=30), compared with those without LGE (n=24), had a longer duration of hypertension, higher 24-hour, daytime and nighttime systolic blood pressure, left ventricular mass index, and plasma NT-proBNP (P<0.001). However, they had comparable T1 mapping measurements including ECV. LGE significantly (P ≤ 0.007) and positively correlated with the duration of hypertension, ambulatory systolic blood pressure and LVMI, while ECV and native T1 were significantly (P ≤ 0.027) and inversely associated with plasma renin activity and positively associated with aldosterone-to-renin ratio. Besides, both LGE and ECV significantly (P ≤ 0.030) and positively correlated with NT-proBNP. Non-targeted metabolomic analysis showed that the amino-acid metabolism, especially the L-glutamate metabolism, significantly differed between patients with LGE and those without LGE and correlated with blood pressure and echocardiographic measurements.ConclusionIn patients with primary aldosteronism, focal replacement fibrosis was associated with cardiac afterload factors such as blood pressure, while diffuse interstitial fibrosis was associated with hyperaldosteronism. The amino-acid metabolism, especially the L-glutamate metabolism, might be involved in the process of myocardial fibrosis.